A Randomized Assessor-Blinded Wait-List-Controlled Trial to Assess the Effectiveness of Acupuncture in the Management of Chemotherapy-Induced Peripheral Neuropathy. (March 2019) - Molassiotis, Alexander; Suen, Lorna K. P.; Cheng, Hui Lin; Mok, T. S. K.; Lee, Sara C. Y.; Wang, C. H.; Lee, Paul; Leung, Howan; Chan, V.; Lau, T. K. H.; Yeo, Winnie
Purpose: Chemotherapy-induced peripheral neuropathy is a complex side effect with few available treatment options. The aim of the study was to test the effectiveness of an 8-week course of acupuncture in the management of chemotherapy-induced peripheral neuropathy in cancer patients who were receiving or had received neurotoxic chemotherapy.Methods: Randomized assessor-blinded controlled trial with 2 arms; one arm received acupuncture twice weekly for 8 weeks, while the other arm was a wait-list control group receiving only standard care. Primary outcome was pain intensity and interference over the past week using the Brief Pain Inventory at the end of the intervention. Secondary outcomes included clinical assessment (CTCAE [Common Toxicity Criteria for Adverse Events] grading and Total Neuropathy Score–Clinical Version) and nerve conduction studies; and patient-reported outcome measures (Functional Assessment of Cancer Therapy–Gynecologic Oncology Group–Neurotoxicity Quality of Life scale and Symptom Distress Scale) assessed at baseline, end of treatment (8 weeks), week 14, and week 20 from the beginning of treatment.Results: Eighty-seven patients were randomized to the experimental arm (n = 44) and to the standard care wait-list control arm (n = 43). Significant changes at 8 weeks were detected in relation to primary outcome (pain), the clinical neurological assessment, quality of life domains, and symptom distress (all P < .05). Improvements in pain interference, neurotoxicity-related symptoms, and functional aspects of quality of life were sustained in the 14-week assessment ( P < .05), as were physical and functional well-being at the 20-week assessment ( P < .05).Conclusions: Acupuncture is an effective intervention for treating chemotherapy-induced peripheral neuropathy and improving patients' quality of life and experience with neurotoxicity-related symptoms with longer term effects evident.